Identifying Characters of âWhere Angel Fear to Tread Novelâ in Teaching Literary Work - Suhaimi, Suhaimi (AT-TALIM, 2016)
The aim of the research is to identify some characters in the novel Where Angels Fear to Tread in teaching literary works. In learning of characters, someone will understand about the term of the interests, desires, emotions, and moral those form the individual within a story. Library research was used in thid study. The experts divide characters become two characters; they are central characters and additional characters. Central characters are a character who takes the greatest part in the main character or a figure that is most telling. Volume appearance of the main character more than the other characters. Meanwhile, additional characters or subordinate figures are figures that appear once or several times, figures that support or assist the central figure. In the novel Where Angels Fear To Tread, writer found some figures or characters such as: Mrs. Herriton, Lilia, Philip, Gino, and Carroline Abbot. Each of them had different characters; Mrs Herriton was a selfish and arrogant because she came from a high social status. Lilia was a patient and never denied what was ruled by her mother in-low although sometimes she was often treated her like slaves. Philip was figured as a handsome man, his tolerance and empathy were high. Gino was figured as stupid character. Miss Abbott as a nice, quiet, dull, and friendly.